O lugar de memória da identidade ficcional em ''Relato de um certo oriente'', de Milton Hatoum - (:unkn) unknown (Universidade Estadual de Goiás, 2019)
This research aims to analyze the novel Relato de um certo Oriente by the Brazilian writer Milton Hatoum, published for the first time in 1989, from a memorialistic and spatial perspective. It is observed how the place of memory of the fictional identity, of the innominate character of the novel is represented by the memory and the lived space, and of how these two aspects are configured as the central axis of the narrative. From the study on memory, this investigation starts from the importance of the topofílico space for the constitution of the identity of the central character who revives in the narrative the moments of his childhood and, thus, he finds himself again, through the writing exercise of the story . The set of dispersed voices of the novel is the axis for its construction that centers in the topofílico space the experiences and memories of the childhood. The house and the city of Manaus have an important role in the novel, to bring the memories of the past to the present. Time lost is rediscovered by memory, which restores the present by reconstituting its identity in it. Memory has the power to restore the steps, the actions practiced by the characters in various spaces. The space of the house is a cradle that houses the reverie and in it the images rebuild. The relevance of the house where the narrator lived in childhood and the places described in Manaus go back to the past. The theoretical discussion focuses on the various knowledge about memory, identity and space. Thus, in memory novels, memories are always situated in time and space. Thus, memory time is the time passed and revisited, in the novel analyzed, through space. In order to analyze the memory, the identity and the fragmentation of the being we use Ecléa Bosi (2003); Jacques Le Goff (2003); Hall (2006); Henri Bergson (1999); As theorists about space and place we have Bachelard (1993); Tuan (1980) and Milton Santos (1998). In this study we analyze from memory and space, a female character who returns to her hometown and sees in this return her identity, before in crisis, to reconstitute herself.
Keywords: Identidade; Espaço; Memória; Topofílico; Relato; Identity; Space; Memory; Topophilic; Story; LINGUISTICA, LETRAS E ARTES